2014
DOI: 10.1016/j.jaac.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Manic Symptoms in Youth: Dimensions, Latent Classes, and Associations With Parental Psychopathology

Abstract: Objective The purpose of the study was to define the latent structure of parent-reported manic symptoms and their association with functional impairment and familial risk in a community sample of Brazilian children. Method We screened for manic symptoms in a community sample of 2,512 children 6 to 12 years of age. Parents of children with “episodes of going abnormally high” completed a detailed mania section (n = 479; 19.1%). Confirmatory factor analysis (CFA) tested a solution with “Under-Control (UC)” and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
6
20
0
Order By: Relevance
“…Our findings accord with previous studies that have identified this constellation of symptoms as a subthreshold bipolar phenotype in the general population (Pan et al, 2014;Stringaris et al, 2011). Moreover, our results are in line with findings of a recent study in offspring of BD parents which examined the predictive value of dimensional symptomatic measures for new-onset bipolar spectrum disorders (Hafeman et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings accord with previous studies that have identified this constellation of symptoms as a subthreshold bipolar phenotype in the general population (Pan et al, 2014;Stringaris et al, 2011). Moreover, our results are in line with findings of a recent study in offspring of BD parents which examined the predictive value of dimensional symptomatic measures for new-onset bipolar spectrum disorders (Hafeman et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The constellation of subthreshold symptoms that define this high-risk phenotype for BD is thought to reflect reduced control over cognition, emotion and behavior (Pan et al, 2014;Stringaris et al, 2011). As disruptive behavior disorders and ADHD are also characterized by dyscontrol symptoms (Martel et al, 2013), it is not surprising that these disorders were common in children in the mildly and highly symptomatic classes (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second-generation antipsychotics (SGAs) approved by the United States Food and Drug Administration (FDA) for the treatment of acute mania and/or mixed mania in children and adolescents (10–17 years) include risperidone, aripiprazole and quetiapine, olanzapine, and asenapine 1317 (http://www.accessdata.fda.gov/scripts/cder/daf/). Lithium has FDA indication for the treatment and recurrence prevention of mania in youths aged 12 years and older, bolstered by a recently published positive 8-week RCT for youths 7–17 years old with BD-I manic/mixed episodes.…”
Section: | Pharmacologic Treatmentmentioning
confidence: 99%
“…In the suicide risk literature, LCA has been used to identify precipitants for suicidal thoughts among adolescents of various ethnic and racial backgrounds (De Luca et al, 2014; Stoep et al, 2009); to predict suicidal behavior (Thompson et al, 2009); to recognize patterns in known risk factors for suicide among suicide decedents (Judd et al, 2012; Kim et al, 2003; Logan et al, 2011); to identify psychiatric disorder subtypes that might be more strongly associated with suicidal thoughts or behaviors (Li et al, 2014; Pan et al, 2014); and to explore interactions among suicide risk factors (Pena et al, 2012). …”
Section: Introductionmentioning
confidence: 99%